Extending Business Opportunities and Smart Services using Machine Learning - K, Suresh; PVGD, Prasad Reddy; P, Pushkal (International Journal of Computer Sciences and Engineering, 2019)
With the advancement of technology and growing business needs it is vital that the services offered to customers across various applications need to be proactive and not reactive. This work extends the existing cloud framework available for smart homes that offers extended potential business opportunities to service providers and optimistic smart services to end users. Based on the defined framework cluster analysis is done to derive the customer segmentation that facilitates smart home service providers to offer efficient services and to improve the product upselling. The predicted energy consumption is derived using linear regression, for the end users to be energy efficient. Here a deeper analysis based on the data generated from devices and smart home applications is carried out to offer proactive consumer services and to have economical energy consumption.